Meta-Analysis the Effectiveness of McKenzie Exercise to Reduce Pain in Patients with Non-Specific Low Back Pain - Sima Asmara Dewa Marya Mahardika Putri; Agus Kristiyanto; Hanung Prasetya (Masters Program in Public Health, 2021)
Background: Low back pain (LBP) is defined as a symptom that cannot be specifically validated. LBP is one of the most common forms of musculoskeletal disorders. Anyone can experience lower back pain throughout his life, because LBP is back pain without any underlying abnormalities. There are many exercises that can be given to treat this LBP, one of which is the McKenzie Exercise. The principle of this exercise is to improve posture to reduce lumbar hyperlordosis. This study aims to analyze the effectiveness of the McKenzie Exercise for pain reduction in patients with non-specific LBP. Subjects and Method: This was a systematic review and meta-analysis carried out with the PRISM flow diagram. Search for articles through journal databases includes: PubMed, Science Direct, Google Schoolar and PEDro by selecting articles published in 2010-2020. The keywords used were (